The incidence of anxiety in patients with chronic subjective tinnitus - Nenad Arsović; Zoran Dudvarski; Gabrijela Šolaja; Ljiljana Krsmanović; Siniša Šolaja; Bojan Joksimović (Биомедицинска истраживања, 2021)
Introduction: Tinnitus is a perception of a sound in the ears in the absence of acoustic stimulation whose pathophysiological mechanisms have not been evaluated yet. Approximately, 1-2% of people report distress which can negatively affect their daily performance. Our study aimed to assess the incidence of anxiety in patients with tinnitus. Methods: The study was designed as a cross-sectional study. The participants were divided into two groups: a group of 73 patients with tinnitus (with two subgroups in relation to the duration of tinnitus-less than one year and more than one year) and a control group of 43 patients without tinnitus. We examined the presence of anxiety in all patients using the Burns Anxiety Inventory (BAI). The quality of life of all patients was estimated by Tinnitus Handicap Inventory (THI). Results: In the group of patients with tinnitus, 56.2% of them had mild and 24.7% moderate hearing loss, while 27.7% of respondents from control group had mild and 8.5% moderate levels of hearing impairment. THI results showed that patients with tinnitus less than 1 year had a significantly (p= 0.002) higher level of disorders in daily life, compared with the group who had tinnitus for more than 1 year. The 30.8% of respondents had minimal anxiety, 26.7% borderline anxiety, 17.5% mild anxiety, the same percentage of respondents moderate, 5% severe, while 2.5% had extreme anxiety based on BAI. Conclusion: Anxiety can be considered as potentially significant modulators of changes in brain structures observed in people with tinnitus.
Keywords: tinnitus; anxiety; Tinnitus Handicap Inventory; Burns Anxiety Inventory